Implementasi Nilai Kemanusiaan Pada Kegiatan Ekstrakurikuler Pramuka Di Smkn 9 Kota Tangerang - Nita Amelya; Suanto Suanto (Journal on Education, 2024)
The implementation of human values in extracurricular scouting activities at SMKN 9 Tangerang City can be seen from the habituation of scout members in scouting activities, as well as their activity programmes. In the implementation of human values, the scouts are provided with materials and activities that contain human values in scouting. They are given an understanding and required to behave politely in accordance with the applicable rules to apply the 5S attitude and are given an intake of educational scout activity programmes as well as having extraordinary experiences in terms of humanity. Supporting factors for the implementation of human values can be seen from the support and role of trainers, coaches, and teachers at SMKN 9 Tangerang City. Scout coaches and trainers always accompany students in every scouting activity and also provide information about scouting. In addition, the school also provides the budget and facilities needed by the scouts to support the implementation of human values.